Transforming Traditional Flavors: Consumer Response to Mung Bean Flour Nastar Cookies - Mulyantari, Enny Mulyantari (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
Mung beans (Vigna radiata L.) are gluten-free legumes that can be processed into flour, offering a healthier and more affordable alternative to wheat flour. This study explores the use of mung bean flour as a substitute for wheat flour in the making of nastar, a traditional Indonesian pineapple-filled cookie. The aim is to evaluate consumer acceptance of mung bean flour nastar in terms of taste, aroma, color, and texture. An experimental method was employed, using a hedonic scale with four levels (Very Like, Like, Dislike, Very Dislike) and organoleptic testing involving 20 respondents. Data were collected through questionnaires and interviews. The findings indicate that mung bean flour nastar is generally well received, especially in terms of taste and color (scoring in the 'very like' category), texture (in the 'like' category), while aroma received a relatively lower preference. These results suggest that mung bean flour can be a viable alternative in traditional cookie production, contributing to flavor innovation while maintaining consumer acceptance.